مجلس الصلح ودوره في حل المشاكل الأسرة :‏ ‏في نظام المحاكم الشرعية بولاية سلانجور /‏ - Luqman al-Hakimi bin Mohammad Ikhsan (Kulliyyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2011)
This study aims at shedding light on facts of Sulh and its role in solving the dispute between husband and wife as well as to evaluate the field of Sulh and procedure in Shari'ah Lower Court and Shari'ah High Court in Selangor. The study attempts to explain the concept of Shari'ah and its legitimacy in the Holy Quran, Sunnah, Ijma', and 'aql. It also to identifies the advantages of Shari'ah for solving family disputes in Selangor Shari'ah Court. Furthermore, the study endeavours to shed light on all Selangor Shari'ah Courts. The study applies inductive method to collect the Fiqhi data as well as the analytical method to look at the opinions of classical and contemporary fuqaha'. The applied field method used discusses the new issues related to Shari'ah in Selangor Shari'ah Court. The study finds several conclusions, among which is to know about the management Shari'ah Council at Selangor Shari'ah Court and role in solving family disputes such as divorce, maintenance, matrimonial property and Hadanah. Shari'ah Council was established in 2001. It is able to solve family disputes in the Selangor Shari'ah Court without bringing it to the Judge. This Council is able to solve delayed cases and limit the accumulation. Thus, it shows the efficiency of Shari'ah which is implemented in Shari'ah Council at all Selangor Shari'ah Courts according to Shari'ah resources and laws in Malaysia